PERFORMANCE ANALYSIS OF FOOTWEAR SENSORS FOR VOLTAGE MONITORING - Muhamad Aiman; Ruzlaini Ghoni; Mohd Tarmizi Ibrahim; Fariyono Fariyono (Teknika, 2025)
Advances in wearable technology are driving innovation in efficient, self-powered biomechanical monitoring systems. One promising approach uses piezoelectric sensors to generate energy while detecting foot (plantar pressure) during physical activity. This study aims to design and test a piezoelectric-based insole system capable of performing dual functions: harvesting mechanical energy from footsteps and analyzing fatigue patterns and gait asymmetry. The research used an experimental approach involving 10 male respondents aged 15–31. Each insole was equipped with four DLAY piezoelectric sensors placed on the heel and forefoot of the right and left feet, and connected to a Raspberry Pi Pico RP2040 microcontroller for voltage data acquisition. The data was analyzed using voltage changes to indicate foot pressure distribution and muscle fatigue. The results showed that the system could generate voltages between 0.025 V and 0.082 V, with an average harvested power of 4.8mW. 70% of respondents experienced decreased voltage in one leg, indicating unilateral fatigue and gait imbalance. Respondent 10 showed the most significant voltage decrease in the left heel sensor (<0.03 V after 1000 seconds), while the right foot remained stable (0.045–0.055 V). In contrast, Respondent 5 showed stable and symmetrical voltage distribution throughout the test session.